"Open States" and citizen incorporation in Government Institutions - Morales Zamorano, Miguel Arturo (UNIVERSIDAD DE SONORA, 2018)
Introduction: Product of an research process, it has left of the following central question: ¿What do spaces, times and resources have the citizenship to be included in the design, execution, control and evaluation of strategies of collaboration with drawees of government decisions?, where we distinguish twovariables: 1. - Spaces, times and citizen resources, as well as 2. - The independent variable of collaboration in government projects